Hypercapnia versus normocapnia for emergence from desflurane anaesthesia: Single-blinded randomised controlled study. Issue 11 (November 2021) - Shinohara, Ayako; Nozaki-Taguchi, Natsuko; Yoshimura, Akiko; Hasegawa, Makoto; Saito, Kei; Okazaki, Junko; Kitamura, Yuji; Sato, Yasunori; Isono, Shiroh
Abstract : BACKGROUND: Rapid emergence from general anaesthesia is desirable only if safety is not sacrificed. Mechanical hyperventilation during hypercapnia produced by carbon dioxide infusion into the inspired gas mixture or by rebreathing was reported to shorten emergence time from inhalation anaesthesia. OBJECTIVES: To test the hypothesis that hypercapnia produced by hypoventilation before desflurane cessation shortens emergence time from general anaesthesia (primary hypothesis) and reduces undesirable cardiorespiratory events. DESIGN: A single-blinded randomised controlled study. SETTING: A single university hospital. PATIENTS: Fifty adult patients undergoing elective abdominal surgery under general anaesthesia using desflurane inhalation and intra-operative epidural anaesthesia. INTERVENTION: The patients were randomly assigned to either the normocapnia or hypercapnia group. MAIN OUTCOME MEASURES: Emergence time from desflurane anaesthesia and comparison of the incidence of 11 predefined undesirable cardiorespiratory events during and after emergence from anaesthesia between the groups. RESULTS: Forty-six patients were included in the analysis. End-tidal carbon dioxide concentrations at cessation of desflurane were 35 ± 6 mmHg (mean ± SD) and 52 ± 6 mmHg in normocapnia ( n  = 23) and hypercapnia groups ( n  = 23), respectively. Emergence time was significantly faster in the hypercapnia group than the normocapnia group: 9.4 ± 2.4 min, hypercapnia: 5.5 ± 2.6 min, ( P  < 0.001) with a difference of 3.8 min on average (95% CI: 2.4 to 5.3). Spontaneous breathing established before recovery of consciousness was more evident in hypercapnia patients (normocapnia: 13%, hypercapnia: 96%, P  < 0.001). Hypercapnia patients had more episodes of bradypnoea and apnoea before emergence of consciousness. In contrast, after tracheal extubation, incidences of bradypnoea and hypopnoea were more common in the normocapnia group. Undesirable cardiovascular events were not common, and no group differences were observed during emergence and postextubation periods. CONCLUSION: Hypoventilation-induced hypercapnia before desflurane cessation shortens the emergence time without causing additional clinically significant undesirable events. TRIAL REGISTRATION: UMIN Clinical Trials Registry (UMIN000020143) https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&recptno=R000023266&language=E